There are two sets of consecutive positive integers where each has a sum of 100. Find the sum of the two numbers that begin each sequence.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
One small shortcut - note that of the two factors k + 1 and k + 2 n , one must be odd and the other even. The only odd factors of 2 0 0 are 1 , 5 and 2 5 .
Let the required set begins with a and ends in b , where a and b are positive integers. Then the sum of the elements of the set is 2 b ( b + 1 ) − 2 a ( a + 1 ) . Therefore b 2 − a 2 + b − a = 2 0 0 , or ( b − a ) ( b + a + 1 ) = 2 0 0 . Now 2 0 0 is the product of (i) 1 and 2 0 0 , (ii) 5 and 4 0 , and (iii) 2 5 and 8 . ( b − a and b + a + 1 are of opposite parity). Hence (i) a = 9 9 , b = 1 0 0 , (ii) a = 1 7 , b = 2 2 , and (iii) a = 8 , b = 1 6 . Therefore the sets are { 1 0 0 }, { 1 8 , 1 9 , 2 0 , 2 1 , 2 2 } and { 9 , 1 0 , 1 1 , 1 2 , 1 3 , 1 4 , 1 5 , 1 6 }. Hence the required answer is 1 0 0 + 1 8 + 9 = 1 2 7
Problem Loading...
Note Loading...
Set Loading...
We need to find all positive n , k such that n + ( n + 1 ) + . . . . + ( n + k ) = 1 0 0 . We can rewrite this equation as
( 1 + 2 + . . . . + ( n − 1 ) + n + . . . . + ( n + k ) ) − ( 1 + 2 + . . . + ( n − 1 ) ) = 1 0 0 ⟹ 2 ( n + k ) ( n + k + 1 ) − 2 ( n − 1 ) × n = 1 0 0 ⟹
( n + k ) 2 + ( n + k ) − n ( n − 1 ) = 2 0 0 ⟹ n 2 + k 2 + 2 n k + n + k − n 2 + n = 2 0 0 ⟹ k 2 + k + 2 n k + n = 2 0 0 ⟹
k ( k + 1 ) + 2 n ( k + 1 ) = 2 0 0 ⟹ ( k + 2 n ) ( k + 1 ) = 2 0 0 .
Now consideration the possible two-element factorizations of 2 0 0 , noting that as n ≥ 1 we must have k + 2 n > k + 1 . These factorizations are
(i) k + 2 n = 2 0 0 , k + 1 = 1 ⟹ k = 0 , n = 1 0 0 , which would only involve one term so we can discard this option,
(ii) k + 2 n = 1 0 0 , k + 1 = 2 ⟹ k = 1 , n = 4 9 . 5 , but we require a sequence of integers, so discard,
(iii) k + 2 n = 5 0 , k + 1 = 4 ⟹ k = 3 , n = 2 3 . 5 , discard as for (ii),
(iv) k + 2 n = 4 0 , k + 1 = 5 ⟹ k = 4 , n = 1 8 , giving us the valid sequence 1 8 , 1 9 , 2 0 , 2 1 , 2 2 ,
(v) k + 2 n = 2 5 , k + 1 = 8 ⟹ k = 7 , n = 9 , giving us the valid sequence 9 , 1 0 , 1 1 , 1 2 , 1 3 , 1 4 , 1 5 , 1 6 ,
(vi) k + 2 n = 2 0 , k + 1 = 1 0 ⟹ k = 9 , n = 5 . 5 , which would not involve a sequence of integers.
So the two valid sequences begin with 1 8 and 9 respectively, giving us a desired answer of 1 8 + 9 = 2 7 .